Impact of high platelet reactivity on left ventricular remodeling in patients with acute coronary syndrome. (14th October 2021) - Tsuji, M; Kuroda, K; Saito, E; Kawamura, K; Ono, T; Tokioka, K; Ohe, T; Kawai, Y
Abstract: Background/Introduction: Previous studies demonstrated that high platelet reactivity (HPR) predicts future cardiovascular death and coronary events in patients undergoing percutaneous coronary intervention (PCI) for acute coronary syndrome (ACS). However, few studies have focused on the impact of HPR on left ventricular remodeling (LVR) and each echocardiographic parameter. Purpose: The purpose of this study was to investigate the impact of HPR in ACS patients on LVR and changes in echocardiographic volume indexes and LV ejection fraction. Methods: This is a retrospective cohort study of prospectively collected data in a single center that enrolled patients who underwent emergency PCI for ACS including STEMI and NSTEMI with prasugrel loading. The primary outcome of the study was LVR associated with HPR. Secondary endpoints were changes in indexed LVESV, LVEDV, LVEF, E/e' and LAVI between baseline and follow-up. The P2Y12 reaction unit (PRU) value in response to prasugrel was assessed by the VerifyNow P2Y12 assay. Blood samples were collected once per procedure immediately after PCI. LVR index was calculated as the relative change in LVEDV observed at follow-up compared with baseline. LVR was defined as a relative increase in LVEDV ≥20%, measured at follow-up visit compared with the baseline value before discharge. Results: A total of 196 ACS patients who underwent emergency PCI between January 2016 and July 2020 were enrolled in the study. The mean age of the study population was 69.9 years, and 76.0% were male. On echocardiography at follow up visit of mean duration of 7.0±4.0 months, LVR was found in 38 patients (19.4%). The optimal cutoff for PRU associated with increased LVR assessed by receiver-operating characteristic curve analysis was 245.5 (AUC: 0.656; 95% CI: 0.564 to 0.749; p=0.003). On the basis of this cutoff, HPR was found in 82 patients (42.1%) and the prevalence of LVR was significantly higher in the HPR group compared to the non-HPR group (30.5% vs. 11.4%; p=0.001). Multiple Cox regression analysis showed that HPR was an independent predictor of LVR (OR 4.22, 95% CI 1.83–9.71, p=0.001). In addition, Δ% EDV and Δ% ESV increased in the HPR group, and decreased in the non-HPR group with significant differences (5.8±32.6% vs. −8.0±26.2% in Δ% EDV; p=0.002, 2.0±37.5% vs. −13.3±33.0% in Δ% ESV; p=0.004, respectively). Δ%EF, Δ%E/e', Δ%LAVI were numerically improved in the non-HPR group compared with the HPR group, but this difference did not reach statistical significance. Conclusion: In patients with ACS, HPR defined as PRU ≥246 immediately after emergency PCI was an independent predictor of LVR in the chronic phase. Funding Acknowledgement: Type of funding sources: None.